Perancangan Prototipe Alat Bermain Belajar Braille Low Cost Berbasis Mikrokontroler Arduino Sensor RFID - Bertha Bintari; Martinus Bagus Wicaksono (Universitas Putra Indonesia YPTK Padang, 2022)
Blind children have limited ability to read, so the introduction of the ability to read and write using braille is very important. They have to learn to recognizing braille letters, then arranging letters to form syllables and finally a word. Learning about the concept of reading needs a tool that makes it easy and fun, then children will learn while playing. The design of the device braille set is intended as a learning tool for blind children to introduce and learn to read braille. This system uses an RFID (Radio Frequency Identification) MFRC522 sensor programmed by Arduino as a microcontroller. The code as a signal in the RFID tag card is read by the RFID reader. RFID tag cards are equipped with a layer on the surface of the card marked with a braille symbol. When children recognize the braille symbols on cards, they can assemble the cards into a word. The word will then be read by the device and audible so that the children hear the words they have composed. The components of this learning tool to read braille use an RFID reader component, a mini MP3 player module, Arduino, as a microcontroller. The power supply uses a 9 volt battery. DC motor drive and wheels to walk on the scrabble track. The material for the card coaster casing uses acrylic material. The track frame uses aluminium profiles. Overall, the cost of making braille reading learning tools with the implementation of RFID technology is cheap and affordable.